From the History of the Church of the Renewal in Ukraine: the 1927 Pre-Council Meeting - Jilyuk, S. I. (Ukrai͏̈ns'ke relihijeznavstvo, 2003)
The activities of the Update (Synodal) Church in Ukraine in national historiography are not covered. Only some of the works show some aspects of state-church and inter-church relations, which only to a certain extent reflect the position of the updated clergy in the general church movement of the 1920s. It remains as important for historians and religious scholars to consider such an important area of ecclesiastical activity as cathedrals or rides of clergy and laity. This article is the first contribution to solving the unexplored part of the problem.